Exploring the Role of Tourism Community Service Programs in Promoting Sustainable Tourism Practices in Lombok Island, Indonesia - Lalu Mohamad Iswadi Athar; Faiza Husnayeni Nahar; Uwi Martayadi (PENTAHELIX: Jurnal Ilmiah Pengabdian Pariwisata, 2023)
This study explores the role of tourism community service programs in promoting sustainable tourism practices in Lombok Island, Indonesia. A qualitative research approach was used to collect data from key informants, including tourism practitioners, policymakers, and community members involved in tourism community service programs. The results of the study indicate that tourism community service programs can play an important role in promoting sustainable tourism practices by empowering local communities, enhancing environmental protection, promoting cultural preservation, and supporting economic development. However, effective implementation requires stakeholder participation, adequate resources and funding, and awareness and understanding of sustainable tourism practices. The study highlights the need for greater stakeholder participation and education in tourism community service programs and the importance of adequate resources and funding for their implementation and sustainability. This study has important implications for promoting sustainable tourism practices in Lombok Island, Indonesia, and similar destinations, and suggests that further research is needed to explore the long-term impact of tourism community service programs and to identify best practices for their implementation and sustainability